Analisis Pengaruh Daya Tarik Iklan di Media Sosial Instagram terhadap Keputusan Pemilihan Hotel - Rusdi Hidayat; Acep Samsudin; Anggun Fatmawati; Adam Firdausi; Dina Aprilia Irawan; Jenny Amelia Gifani; Naura Husnina Athifanita Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
At this time, technology is growing and the competition between companies is getting tougher. With the development of technology, more and more hotels with good quality are created. Various factors can influence consumer decisions in choosing a hotel, one of which is advertising on social media, especially Instagram. Advertising on Instagram can influence consumer decisions in hotel selection, this can affect the image of the selected hotel. If a hotel has increased consumers, it will be seen by the community that the hotel has good quality and vice versa. The purpose of this study was to determine the effect of the attractiveness of advertising on Instagram media on hotel selection decisions. The research method used in this research is the library research method. The results of this study indicate that Instagram has a significant role in the marketing process of the hospitality industry so that it can increase consumer attractiveness in hotel selection. Instagram has a very wide audience coverage which has a huge impact on customer decisions. Keywords: hotel, instagram, decision, marketing